2003
DOI: 10.1038/sj.bjc.6601112
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in B-cell non-Hodgkin lymphomas is regulated by hTERT transcription and correlated with telomere-binding protein expression but uncoupled from proliferation

Abstract: Telomere maintenance is a prerequisite for immortalisation, and in most malignant cells is carried out by telomerase, an enzyme that synthesises new telomeric repeats on the chromosome ends. In normal or reactive tissues with a high regenerative capacity, telomerase is regulated according to the telomere loss that occurs during proliferation. To evaluate the interaction of proliferation and telomerase activity in malignant lymphomas, we quantified telomerase expression in different non-Hodgkin lymphomas in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 40 publications
1
34
4
Order By: Relevance
“…Analysis of the telomere binding proteins revealed that TERF1, TERF2, and tankyrase expression was similar across the benign tissue and the malignant samples although, interestingly, levels of the helicase hPif1, known as a telomerase inhibitor, were increased in the BL samples. Klapper et al (2003) suggested that the likely reason for the discrepancy in their findings to the previously published studies was due to the use of non-quantitative TA assay in the earlier studies. Their method used an internal control to produce a semi-quantitative measurement that was then further investigated by analysing TERT expression (Klapper et al, 2003).…”
Section: B-cell Lymphomascontrasting
confidence: 53%
See 3 more Smart Citations
“…Analysis of the telomere binding proteins revealed that TERF1, TERF2, and tankyrase expression was similar across the benign tissue and the malignant samples although, interestingly, levels of the helicase hPif1, known as a telomerase inhibitor, were increased in the BL samples. Klapper et al (2003) suggested that the likely reason for the discrepancy in their findings to the previously published studies was due to the use of non-quantitative TA assay in the earlier studies. Their method used an internal control to produce a semi-quantitative measurement that was then further investigated by analysing TERT expression (Klapper et al, 2003).…”
Section: B-cell Lymphomascontrasting
confidence: 53%
“…Klapper et al (2003) suggested that the likely reason for the discrepancy in their findings to the previously published studies was due to the use of non-quantitative TA assay in the earlier studies. Their method used an internal control to produce a semi-quantitative measurement that was then further investigated by analysing TERT expression (Klapper et al, 2003).…”
Section: B-cell Lymphomascontrasting
confidence: 53%
See 2 more Smart Citations
“…Dysfunctional telomeres may arise either from critically short telomeres or by disruption of the shelterin complex [28]. In some hematologic malignancies, altered expression of shelterin proteins might disrupt the telomere structure, contributing to malignant transformation [13,[28][29][30][31]. Particularly in MCL, to our knowledge, there is only one report on the expression levels of TRF1, TRF2, TNKS, and PIF1 in a limited number of patients (7-8 cases) [30] and no differences in gene expression were found in comparison to lymph nodes.…”
Section: Discussionmentioning
confidence: 99%